Impact of Competition and Taxes on Responsibility Center Organization and Transfer Prices* - NARAYANAN, V. G.; SMITH, MICHAEL (Contemporary Accounting Research, 2000)
We show that a firm can use its decentralized organizational structure and transfer price as commitment devices to obtain strategic advantage in the product market only when there are nonstrategic reasons to decentralize and to distort transfer prices away from marginal costs, such as the sales office's local knowledge about market conditions and the presence of tax rate differentials across the two tax jurisdictions. Surprisingly, an increase in the sales office's tax rates may help a firm increase overall profits. An increase in the sales office's tax rates causes the firm to increase its transfer price, which in turn dampens the sales office's competition and may more than offset the effect of increased tax rates on the firm's overall profits.